Alarming Pandrug Resistance (PDR), Extensive Drug Resistance (XDR), and Multidrug Resistance (MDR) Gram-Negative Bacilli (Journal of Current and Advance Medical Research, 2015)
No Abstract AvailableJournal of Current and Advance Medical Research 2015;2(1):1-2DOI:http://dx.doi.org/10.3329/jcamr.v2i1.22578